Human papillomavirus type 16 genomic variation in women with subsequent in situ or invasive cervical cancer: prospective population-based study - Arroyo-Mühr, Laila Sara (Br J Cancer, 2018)
BACKGROUND: HPV genomic variation may be involved in viral carcinogenesis. METHODS: In a national register-based nested case–control study, we retrieved archival smears from baseline cytologically normal women who later developed cancer in situ (CIS), squamous cervical cancer (SCC) or remained free of disease. These smears were previously HPV tested by PCR and HPV16 was the strongest risk factor. We now used the Illumina NextSeq platform to sequence HPV16 genomes in cervical smears from 242 women who later developed CIS/CIN3 (n = 134), SCC (n = 92) or remained healthy (n = 16). RESULTS: The median sequence depth per sample was high (11,288×). For 218/242 samples (>90%), we covered ≥80% of the complete HPV16 genome with sequencing median depths of >200×. We identified a wide range of unique isolates and 147 novel SNPs across the 218 samples. Most women (97%) had HPV16 lineage A infection, with the sublineages being A1 (66.1%), A2 (28.9%) and A4 (1.8%), respectively. The least variable gene was the E7 (3.4% variability), where 170/204 case women (83%) displayed a fully conserved sequence. There were no obvious differences by disease outcome (CIS or SCC). CONCLUSIONS: We found a high number of novel SNPs. The E7 gene was hypovariable both among women later developing CIN3/CIS, and SCC, respectively.